Competititve strategy of taxi company in facing environmental changes - Athoillah, Ahmad Saifi; Firdaus, Muhammad; Sanim, Bunasor (BISMA (Bisnis dan Manajemen), 2019)
This study aims to analyze the satisfaction of taxi passengers, the internal and external factors in PT XYZ and formulate the competitive strategy with conventional taxi competitor and online taxi companies. The scope of this research is specifically focused on the competitive strategy in strategic business unit level. This study uses quantitative descriptive approach. The data analysis techniques used are IFE, EFE, IE, and QSPM. The result of this study on the analysis of EFE, PT XYZ shows that the highest strength is on a strategic distribution network of taxi in big cities. Meanwhile, the highest threats are standardization of tariff, number of taxi, and minimum identity of online taxi. Furthermore, IE matrix analysis shows that PT XYZ is in quadrant I (grow and build strategy). The decision making stage based on QSPM matrix has the order of strategic priority as follows: forward integration, backward integration, horizontal integration, product development, market penetration, and market development. Keywords EFE; IFE; IPA; QSPM; strategy competitive